The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.agwat.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and reclamation of a biochar and compost amended saline–sodic soil with moderate SAR reclaimed water

Abstract: a b s t r a c tRemediating saline-sodic soils with organic amendments is increasingly seen as a cheaper and sustainable alternative to inorganic materials. The reclamation potential of biochar, biosolids and greenwaste composts applied to a saline-sodic soil was evaluated in a laboratory leaching experiment using moderate SAR reclaimed water. Treatments included biochar, biosolids co-compost, greenwaste compost (all applied at a 75 t ha −1 rate), gypsum (50% soil gypsum requirement), biochar + gypsum, biosolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
76
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(110 citation statements)
references
References 79 publications
21
76
1
1
Order By: Relevance
“…The H + from the acidified biochar and Ca 2+ ions from either the dissolution of calcite or the biochar itself helps to replace Na + on soil colloid and finally Na + excluded from the soil (Figure ). This result was in agreement with results of Chaganti et al (), who indicated that using biochar decreased soil Na + concentration. Also, Akhtar, Andersen, and Liu () reported that the application of biochar significantly decreased the Na + concentration of salt‐affected soil.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The H + from the acidified biochar and Ca 2+ ions from either the dissolution of calcite or the biochar itself helps to replace Na + on soil colloid and finally Na + excluded from the soil (Figure ). This result was in agreement with results of Chaganti et al (), who indicated that using biochar decreased soil Na + concentration. Also, Akhtar, Andersen, and Liu () reported that the application of biochar significantly decreased the Na + concentration of salt‐affected soil.…”
Section: Resultssupporting
confidence: 94%
“…Acidification of soil likely induced release of surplus of Ca 2+ , Mg 2+ , and Cl − into leachates. This result is in line with result of Chaganti et al (). However, the concentration of HCO 3 − in leachates of acidified biochar‐treated soils was enhanced gradually, which might be due to dissociation of carbonic acid to HCO 3 − and H + .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It is important to note that the soil column experiment in the present study was performed on homogeneous soil and melting temperatures, whereas soil spatial heterogeneity is usual for chemical and physical properties, including water, salt and soil pores, which influence hydraulic conductivity and the rate of infiltration of melting saline ice (Assouline, ; Carvalho, Eduardo, Almeida, Santos, & Sobrinho, ; Dafny & Šimůnek, ). The above factors all further influence the salt leaching effect in saline soil (Chaganti et al, ). Moreover, the different infiltration processes among treatments in the present study suggested changes in soil hydraulic conductivity, which is mainly affected by cation exchange capacity (Mandal et al, ), soil structure (Alrajhi et al, ), aggregate stability (Suarez et al, ), clay dispersion (Moreno et al, ) and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated values of the sodium adsorption ratio (SAR) of the source water can lead to a reduction in hydraulic conductivity and rate of infiltration (Suarez, Wooda, & Lesch, 2006). In addition to the source water, initial soil properties such as the soil water content and degree of soil porosity, are important factors that influence saline water infiltration (Ahmed et al, 2012;Alrajhi, Beecham, & Hassanli, 2017;Chaganti, Crohn, & Simunek, 2015). Smaller initial soil water content and bulk density favour saline water infiltration and salt leaching from the soil (Chaganti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%